Ultimate Book of Animals - Baumann, Anne-Sophie (France : Twirl/Bayard Group, 2021)
Creatures of land, sea and air - from the tiny hummingbird to the enormous blue whale - fill the pages of this interactive book. Pull tab, lift the flap, open for a 3-4 look, turn the wheel and have fun learning!
110180
Keywords: Eleonore Della Malva -- Illustrator; Animals -- Children's picture books; Toys and moveable books. -- Children's picture books; Mammals; Reptiles; Birds; Ocean life